Palm oil contains carotenoid about 500-700 ppm. Epidemiology study showed that carotenoids are beneficial for health, but most of carotenoids are destructed and loss during purification of palm oil, so need to be modified to minimize the loss and destruction of carotenoids. One of the methods was to use NaOH to neutralize free fatty acid after degumming step. The aim of this research was to determine optimum condition of deacidification process of palm oil to minimize the destruction of carot - Fajriyati Mas’ud; Tien R. Muchtadi; Purwiyatno Hariyadi; Tri Haryati (Forum Pasca Sarjana, 2008)
Palm oil contains carotenoid about 500-700 ppm.  Epidemiology study showed that carotenoids are beneficial for health, but most of carotenoids are destructed and loss during purification of palm oil, so need to be modified to minimize the loss and destruction of carotenoids.  One of the methods was to use NaOH to neutralize free fatty acid after degumming step.  The aim of this research was to determine optimum condition of deacidification process of palm oil to minimize the destruction of carotenoids.  This research used Central Composite Design (CCD).  Response surface model was applied to see influence of treatment to rendemen, free fatty acid and carotenoids contents of neutralized palm oil (NPO) with three variables of temperature, time, and consentration of NaOH.  This research showed the optimum condition of deacidification process of palm oil to minimize the destruction of carotenoids, i.e. temperature of 59oC, time 25 minutes, and NaOH 11.1% (16oBe).  In this condition the content of  NPO was 95%, with 0.16% of free fatty acid  and total carotenoids of 390 ppm.     Key words: palm oil, deacidification, carotenoid